Efektivitas Model Pembelajaran TGT (Team Games Tournament) dalam Penulisan Puisi di Kelas II SDN Kedunggalar - Uci Ulfa Nur’afifah (LP. Ma'arif Janggan Magetan, 2023)
This research was motivated by the low poetry writing performance of students in the Indonesian language subject, particularly in the poetry section, in the second grade of SDN Kedunggalar. One proposed solution to address this issue was to implement the Team Games Tournament (TGT) teaching model. The aim of this research was to describe the improvement in poetry writing skills in the Indonesian language, specifically in the poetry section, among second-grade students at SDN Kedunggalar through the application of the TGT teaching model. The research employed a quantitative methodology, conducted through a series of phases including planning, implementation, observation, reflection, and data collection. The study was carried out in January 2022, involving 32 second-grade students, consisting of 15 males and 17 females. Data collection methods included documentation, observation, and testing. The results of the research indicated that the poetry writing skills of the students in the Indonesian language, poetry section, in the second grade at SDN Kedunggalar were significantly improved. This was reflected in the post-test results of the experimental group, which had an average score of 94.44 and a median score of 95.0. This represented an 80% improvement after the intervention. In conclusion, it can be inferred that the utilization of the TGT teaching model effectively enhanced the learning effectiveness of poetry writing skills among second-grade students in the Indonesian language subject, specifically in the poetry section, at SDN Kedunggalar.